Spatial Occurrence and Morphological Colony Variability of Bipolaris sorokiniana Isolates Causing Spot Blotch of Wheat in Nepal - Aryal, Laxman; Shrestha, Sundar Man; Manandhar, Hira Kaji; Thapa, Dhruba Bahadur (Journal of Agriculture and Forestry University, 2026)
Bipolaris sorokiniana (Sacc.) Shoem. is an important pathogen causing spot blotch in wheat. A study was conducted to explore the occurrence and morphological colony variability of B. sorokiniana. A total of 36 isolates from single spore were maintained from the disease sample collected from different wheat growing regions of Nepal. Among them, 27 isolates were from terai region; 7 were from mid hill region and 2 were from high hill region. Radial mycelia growth of all the isolates differed significantly at different days after incubation (DAI). Mean colony diameter at 2 DAI, 4 DAI, 6 DAI and 8 DAI were 2.70 cm, 5.54 cm, 7.82 cm and 8.68 cm respectively. Radial mycelia growth ranged from 7.23 cm to 9 cm after 8 days of incubation. Based on colony color, isolates were categorized into 5 groups. Dull/white greenish black had maximum frequency (33.3%) and white colony had minimum frequency (5.5%). Based on colony growth behavior, 41.6% isolates were suppressed growth; 38.8% were fluffy growth and 19.4% were cottony growth. Variability was also observed in colony growth margin where 66.6% isolates were having regular colony margin and 33.3% isolates were having irregular colony margin. Diverse spatial occurrence and high morphological colony variation suggests that isolates of B. sorokiniana causing spot blotch disease might possess different level of virulence profile.